Platelet function defects and sertraline‐induced bleeding: a case report. (18th March 2020) - Strumia, Mathilde; Guerrero, Felipe; Maurel‐Ribes, Agnès; Garcia, Cédric; Payrastre, Bernard; Bagheri, Haleh
Abstract: A 71‐year‐old man is admitted for nose bleeds recurring for several days. His medical background shows in particular major depression for which he has been receiving sertraline for several years. The workup shows anemia, and no anomalies on head and neck CT angiography. However, further explorations suggest an acquired thrombopathy that could have contributed to the bleeding. During sertraline exposure, platelet functional exploration and platelet secretion were abnormal. Sertraline is often used as first‐line treatment of depression. Pharmacological data and spontaneous notifications suggest increased potential risk with sertraline. It appears necessary to pay attention to bleeding with sertraline use.